Educação, qualidade de vida e doença de Alzheimer : visões de idosos e seus familiares - Inouye, Keika (Universidade Federal de São Carlos, 2008)
The purpose of the present was to identify perception differences regarding the quality of life (QL) of a group of aged patients with Alzheimer Disease (AD) and their family caregivers compared to groups who do not have the disease; and, consequently, identify the QL dimensions that merit more attention in psychoeducational intervention problems according to their perspective. The participants were subjects with 60 years of age or more, with no serious language disorders and who had been diagnosed with AD according to the current criteria in the Brazilian legislation, their respective family caregivers and people with equivalent age, gender, and home address. The participants were divided into four groups: GAD: aged individuals with AD (n=53); GADC: elderly without AD (n=53); GCARE: family caregivers (n=53); and GCAREC: non-caregivers (n=53). The instruments used for data collection were: Participant Characteristics Form; Interview Script; Brazil Criteria Questionnaire; and Evaluation Scale for Quality of Life in Alzheimer s Disease (QoL-AD). The obtained data were typed into a databank using the Statistical Program for Social Sciences for Windows 10.0 for statistical analyses (Student s t-test, and Pearson s Chi-square for matched group analyses; Wicoxon, Mann-Whitney, and Spearman Correlation for objectives). The results showed that: (a) the socio-demographic profile of the sample of aged patients with AD is predominantly women, married, with children, illiterate or with incomplete elementary school, from classes C or D , do not exercise, and have no access to alternative health services like occupational therapy, physiotherapy, and psychological treatment; (b) in general, the family caregiver dedicates him or herself full-time to looking after the patient; they are women, wives or daughters, from classes C or D , who find their strongest encouragement regarding QL in sharing the tasks of looking after the patient, in religious groups, or exercising; (c) there are significant differences between the total QL score of aged patients with AD and their family caregivers compared to equivalent samples; (d) there is a correlation between the general QL perception of the aged patient with AD and his or her family caregiver (r=0.406); (e) the general scores obtained by the QoL-AD in the family version about the elderly are not statistically different from those in the version of the aged patient, however the dimensions memory and you in general presented statistically significant differences; (f) the QL dimensions perceived with more negativism and, which, therefore, merit attention in the intervention programs are: for family caregivers: physical health, disposition, mood, memory, you in general, and the ability to take part in leisure activities; and for the elderly patients with AD: physical health, disposition, mood, housing, memory, family, marriage, friends, you in general, the ability to perform chores and take part in leisure activities, money, and life in general. The study findings contribute in making the patient and caregiver education be grounded on their own views, preparing them to cope with dignity the constant changes that time and the environment pose on their bodies, histories, and skills and abilities. Through joint efforts, we can develop interventions to guarantee that negative values and stereotypes associated with AD be assigned new meanings.
Keywords: Educação especial; Qualidade de vida; Alzheimer, Doença de; Idosos; Cuidadores; Education; Quality of life; Alzheimer disease; Aged; Caregiver; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL